Optimization model of collective nutrition in the Serbian Armed Forces using linear programming and Python programming environment - Jović, Saša; Nikolić , Srboljub; Stanković, Ljiljana (Anali Ekonomskog fakulteta u Subotici, 2026)
The aim of this paper is to develop an optimization model of collective nutrition of soldiers based on linear programming, in order to minimize the cost of daily ration while meeting the energy, nutritional and logistical limitations of the military food system. The research was conducted using linear programming, multi-criteria analysis and deterministic sensitivity analysis. The model was implemented in a Python programming environment, and the analysis included 230 dishes from the Diet Plan of the Serbian Armed Forces, including economic, nutritious and organizational restrictions and price change scenarios. The results of the research indicate that the optimization approach enables lower costs of a daily meal compared to the existing normative model, without violating the defined nutritional standards, with satisfactory stability of the model in different market conditions. The originality of the work is reflected in the development of an integrated model that combines economic, nutritional and logistical criteria into a single framework adapted to the military food system. The limitations of the research relate to the deterministic character of the model, static nutritional parameters, and the absence of full stochastic optimization.